Aloe Polysaccharides Inhibit Influenza A Virus Infection—A Promising Natural Anti-flu Drug - Sun, Zhenhong; Yu, Cuilian; Wang, Wei; Yu, Guangfu; Zhang, Tingting; Zhang, Lin; Zhang, Jiguo; Wei, Kai (Frontiers in Microbiology, 2018)
Influenza A virus causes periodic outbreaks and seriously threatens human health. The drug-resistant mutants have shown an epidemic trend because of the abuse of chemical drugs. Aloe polysaccharides extracted from Aloe vera leaves have evident effects on the therapy of virus infection. However, the activity of APS in anti-influenza virus has yet to be investigated. Here, we refined polysaccharides from A. vera leaf. In vitro test revealed that APS could inhibit the replication of a H1N1 subtype influenza virus, and the most obvious inhibitory effect was observed in the viral adsorption period. Transmission electron microscopy indicated that APS directly interacted with influenza virus particles. Experiments on PR8 (H1N1) virus infection in mice demonstrated that APS considerably ameliorated the clinical symptoms and the lung damage of the infected mice, and significantly reduced the virus loads and mortality. Our findings provided a theoretical basis for the development of novel natural anti-influenza agents.